Psychoanalysis of lawyers: high risk for their mental health - Martinez Valera, Pedro Enrique (2024)
Practising lawyers are at high risk for mental disorders and serious family imbalances. Their profession involves them in constant problems and conflicts, which give rise to feelings of depressive and persecutory guilt. Due to their top-down, rote university (de)education with little critical reflection, they suffer from anxiety, depression, addictions and personality disorders, either overtly or covertly. Recent research in Spain, the United States and Brazil has not only shown this, but also feelings of loneliness, dissatisfaction, low self-esteem and professional desertion. In Peru, this situation exists with the aggravating factors of sedentary lifestyles, overweight, obesity and cardiovascular diseases. However, it is only spoken about in hushed tones, as it is a taboo subject. It is therefore urgent that law schools and bar associations carry out mental health prevention programmes.